Periodontal conditions in a 65-year-old population and prevalence of periodontitis according to three different bone level thresholds - Anne Thea Tveit Sødal; Lene Hystad Hove; My Tien Diep; Rasa Skudutyte-Rysstad; Odd Carsten Koldsland (BMC, 2022)
Abstract Aims The aims of this cross-sectional study were to describe the prevalence and severity of periodontal disease in a 65-year-old population in Oslo, Norway, and to investigate to what extent the radiographic bone level threshold for periodontitis case definition influences the prevalence. Materials and methods A random sample of 454 subjects underwent a clinical and radiographic examination and answered a questionnaire regarding general health, medications, and smoking habits. Clinical periodontal parameters (periodontal pocket depths, bleeding on probing, mobility, and furcation involvement) and radiographic bone loss were used to identify periodontitis cases and to assess periodontal stage and grade. Results Of the 454 participants, 52.6% were defined as "periodontitis cases". Of the total study population "unstable cases of recurrent periodontitis" were present in 38.1%, 16.5% of the participants were assigned to stage II, 32.8% to stage III, and 3.3% to stage IV. When lowering the radiographic bone loss cutoff from > 3 mm to > 2 mm or > 1 mm the prevalence of periodontitis increased to 91.9% and 99.6%. Conclusions Periodontitis was common among 65 year-olds living in Oslo, and in the majority of those with periodontitis, the disease was recurrent and unstable. This study also shows that the choice of bone loss cutoff for defining a periodontitis case affects the prevalence estimates to a large extent. In addition, this study addresses weaknesses in the use of the consensus report of the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions for epidemiologic studies in its current form.